Exploring the Role of Principal Leadership in Enhancing School Quality: Insights from “Sengkang” - Said, Rahmat; Lukman, Lukman; Sutriman, Sutrisman; Upe, Ambo (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2024)
This study investigates the impact of democratic leadership on school quality at UPTD SMP Negeri 6 Sengkang. Using a qualitative approach, including interviews, focus groups, observations, and document analysis, the research reveals that the principal’s democratic leadership style significantly enhances school adaptability and development. The principal’s collaborative decision-making and inclusive environment have led to notable improvements in school quality, especially during the challenges of COVID-19. Key findings include increased student enrollment, improved school reputation, and effective management practices. The principal’s clear vision, strong work ethic, and focus on a student-centered approach, alongside teacher professional development and a dynamic curriculum, have been essential in achieving educational goals. The study underscores the importance of democratic leadership in fostering a positive school culture and driving continuous improvement, highlighting the interplay between leadership style and effective school management in promoting educational success.